Observation of electromagnetic GAMs excited by NBI in EAST. (3rd July 2018) - Xu, Ming; Zhang, Jizong; Zhou, Tianchun; Duan, Yanmin; Hu, Liqun; Li, Yingying; Xu, Liqing; Shi, Tonghui; Liu, Yong; Mao, Songtao; Huang, Juan
Abstract: Energetic ions induced electromagnetic geodesic acoustic modes (EGAMs) instabilities during the modulated injection of neutral beams of NBI1 L and NBI1 R have been observed in EAST. The EGAMs coexist with the lower frequency modes (LFMs) instabilities: the frequencies are constant in the radial direction for EGAMs in the range of, while LFMs are located in the range . The density perturbation for EGAM is nearly up-down anti-symmetric, while the magnetic perturbation for EGAM that is standing wave with a principal m   =  2 lobe, and an m   =  4 side-lobe is commonly observed for . EGAMs have strong correlations with the injections of energetic ions, and the toroidal rotation velocity is partially suppressed by the mode excitations, while the magnetic islands of LFM instabilities can form the configuration of 'hollow' structure for . The most pronounced feature of the EGAMs is that the magnetic fluctuations are not antisymmetric in the poloidal angle θ, and they can be expressed as, and the is a function of the pitch angle and energy of energetic ion. The new structure of asymmetry for EGAM has been observed when, where the radial structure extends outward in bottom section, and also exhibits non-uniformity in the toroidal direction, and one possible explanation for the asymmetry is that EGAM are modulated by LSW instabilities with frequency 0  <   f x   <  4 kHz.